Impact Reduction Factors of Energy-Absorbing Rubber Support as a Component in Elastic Flooring System - M. Faiz, S. Aaminah; Abdul Ghani, Abdul Naser (International Journal of Sustainable Construction Engineering and Technology, 2020)
The popularity gained in martial arts raises the concern on the vitality to provide safety during the martial arts practice. Among numerous martial arts, Taekwondo and Karate are recorded to have the highest number of injuries; dominantly occurring in lower limbs due to repeated and prolonged impact force from landing, braking, sudden deceleration and change of direction. Physical lower limb injuries are asserted to be affected upon contact with sport surfaces with ground impact force. The aim of this paper is to design and evaluate a proposed elastic flooring system which comprises of a plywood board (as the upper member) with rubber supports (as the lower member for energy-absorbing). First, the dynamic characterization of the elastic rubber pads for different sizes were conducted using compression test set up. Then, drop test using a drop test set up comprising of 20 kg load and accelerometers were carried out. Dropped at 55mm height constantly for all the floor design based on different impact reduction factor treatments, the acceleration for all the drop tests were recorded. Manipulating on several impact force reduction variation on the lower member, identified as; number of rubber support (X), gap between rubber supports (Y), size of rubber support (Z) and thickness of rubber support (T), an experimental study utilizing sensors and instrumentation is done based on eight samples of the proposed flooring system. The results revealed a positive result on reduction of ground impact by almost 50% significantly, produced by the floor sample using 8 Nos of 0.15mÂ² sized rubber supports with 50mm thickness arranged in 50mm gaps.